Movement disorders in GLUT1 deficiency syndrome respond to the modified Atkins diet. Issue 10 (25th June 2013) - Leen, Wilhelmina G.; Mewasingh, Leena; Verbeek, Marcel M.; Kamsteeg, Erik‐Jan; van de, Bart P.; Willemsen, Michel A.
ABSTRACT Background Movement disorders are a prominent feature of glucose transporter‐1 (GLUT1) deficiency syndrome (GLUT1DS). First‐choice treatment is a ketogenic diet, but compliance is poor. We have investigated the effect of the modified Atkins diet as an alternative treatment for movement disorders in GLUT1DS. Methods Four patients with GLUT1DS ages 15 to 30 years who had movement disorders as the most prominent feature were prospectively evaluated after initiation of the modified Atkins diet. Movement disorders included dystonia, ataxia, myoclonus, and spasticity, either continuous or paroxysmal, triggered by action or exercise. Duration of treatment ranged from 3 months to 16 months. Results All patients reached mild to moderate ketosis and experienced remarkable improvement in the frequency and severity of paroxysmal movement disorders. Cognitive function also improved subjectively. Conclusions The modified Atkins diet is an effective and feasible alternative to the ketogenic diet for the treatment of GLUT1DS‐related paroxysmal movement disorders in adolescence and adulthood. © 2013 International Parkinson and Movement Disorder Society